Combination of temporomandibular disorder and trigeminal neuralgia in adolescent: a case report: Kombinasi gangguan sendi temporomandibular dan trigeminal neuralgia pada remaja: laporan kasus - Ariyanti Rezeki; Laura Susanti Himawan; Ira Tanti; Nina Ariani (Makassar Dental Journal, 2022)
Trigeminal neuralgia was uncommon in people younger than 30 years of age. Only 1% of cases reportedly occurring in those younger than 20 years of age, so that this case is quite rare. The diagnosis of temporomandibular joint disorder (TMD) was also present along with the trigeminal neuralgia and confirmed by head and TMJ MRI. This article describes a case of a 17-years-old females who sought help because of pain in the right side of her face, from her temple area down to her cheek and TMJ, continuing to her lower jaw and sometimes at the back of the ear. She also reported increased pain during chewing or otherfunctional activity. The pain already lasted for almost two years and debilitating. The patient was treated with the combi-nation of pharmacotherapy for treating the trigeminal neuralgia, physical therapy (jaw exercise) and stabilization appliance, in order to reduce the pain and restore the normal function of the lower jaw.It was concluded that trigeminal neuralgia and TMD can be treated simultaneously and obtained a good result.